An easy methodology for frost tolerance assessment in olive cultivars - Valverde, Pedro; Lodolini, Enrico Maria; Giorgi, Veronica; Garcia-Lopez, Maria Teresa; Neri, Davide (Frontiers in Plant Science, 2024)
The cultivation of olive cultivation, like other evergreen fruit crops worldwide, is constrained limited by the specific occurrence of frost episodes inat different times of the year and, although mainly in the middle of winter or early spring. Some contradictory results exist are reported about cultivars' response to frost, which depends on the physiological stage of the tissues (acclimated or not-acclimated) when the cold or frost episode occurs. This work aimed toat implementing a user-friendly andbut reliable lab method for discerning frost tolerance across olive cultivars. Our methodology considered both detached leaves and potted plantlets. The optimal temperature at which damage differentiated between cultivars was evaluated, as well as the time of exposure to cold and the recovery time for the correct evaluation of the symptoms. Furthermore, a comparative analysis of damage on both immature young and mature leaves was conducted. To validate the efficacy of the methodology, we conducted evaluationsassessments were conducted on the cultivars Arbequina (resistanttolerant), Picual (moderately resistanttolerant), and Frantoio (susceptible) under acclimated and non-acclimated conditions. Results indicated that when detached leaves were used for frost evaluation, temperature of -10±1ºC for 30 minutes and recovery time at 26°C for 24-48 hours after exposure to cold are enough to induce damages on the leaves and discriminate between cultivar susceptibility. Under these conditions, a precise assessment of symptoms can be made, facilitating the categorization of frost tolerance level in various olive cultivars. Notably, no significant differences were observed between immature young and mature leaves duringin the evaluation process. On the other hand, the critical temperature to assess damages on potted plantlets was determined to be -7±1ºC. In addition, it was observed that acclimated plants exhibited fewer symptoms compared to non-acclimated ones, with 'Frantoio' being the most affected alongside 'Picual' and 'Arbequina'. The implemented methodology will allow the evaluation assessment of frost tolerance in several olive cultivars within a short timeframe, and it is proven to be user-friendly and reliable.